Periplocymarin Induced Colorectal Cancer Cells Apoptosis Via Impairing PI3K/AKT Pathway - Cheng, Yi; Wang, Guiying; Zhao, Lianmei; Dai, Suli; Han, Jing; Hu, Xuhua; Zhou, Chaoxi; Wang, Feifei; Ma, Hongqing; Li, Baokun; Meng, Zesong (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancers worldwide, and approximately one-third of CRC patients present with metastatic disease. Periplocymarin (PPM), a cardiac glycoside isolated from Periploca sepium, is a latent anticancer compound. The purpose of this study was to explore the effect of PPM on CRC cells. CRC cells were treated with PPM and cell viability was evaluated by CCK-8 assay. Flow cytometry and TUNEL staining were performed to assess cell cycle and apoptosis. Quantitative proteomics has been used to check the proteins differentially expressed by using tandem mass tag (TMT) labeling and liquid chromatography–tandem mass spectrometry. Bioinformatic analysis was undertaken to identify the biological processes that these differentially expressed proteins are involved in. Gene expression was analyzed by western blotting. The effect of PPM in vivo was primarily checked in a subcutaneous xenograft mouse model of CRC, and the gene expression of tumor was checked by histochemistry staining. PPM could inhibit the proliferation of CRC cells in a dose-dependent manner, induce cell apoptosis and promote G0/G1 cell cycle arrest. Total 539 proteins were identified differentially expressed following PPM treatment, among those there were 286 genes upregulated and 293 downregulated. PPM treatment caused a pro-apoptosis gene expression profile both in vivo and in vitro, and impaired PI3K-AKT signaling pathway might be involved. In addition, PPM treatment caused less detrimental effects on blood cell, hepatic and renal function in mice, and the anti-cancer effect was found exaggerated by PPM+5-FU combination treatment. PPM may perform anti-CRC effects by promoting cell apoptosis and this might be achieved by targeting PI3K/AKT pathway. PPM might be a safe and promising anti-cancer drug that needs to be further studied.